Workplace aggression against healthcare workers in a Spanish healthcare institution between 2019 and 2021: The impact of the COVID-19 pandemic - Díaz, Aitor; Utzet, Mireia; Mirabent, Joan; Diaz, Pilar; Ramada, Jose Maria; Serra, Consol; Benavides, Fernando G. (Frontiers in Public Health, 2023)
Objectives Describe the incidence of first aggressions among healthcare workers (HCWs) before and during the COVID-19 pandemic in a Spanish healthcare institution, according to workers' socio-occupational characteristics and analyze the impact of the pandemic on it. Methods A cohort involving HCWs who worked in the institution for at least 1 week each year from 1 January 2019 to 31 December 2021. Adjusted relative risks (aRR) were estimated using generalized estimating equations and negative binomial models to calculate the differences in WPA between the different time periods. All analyses were stratified by gender. Results Among women, the incidence was 6.8% (6.0; 7.8) during the pre-COVID-19 period, 6.0% (5.2; 7.0) during the COVID-19 baseline and 5.1% (4.3; 5.9) during the COVID-19 endline; and 4.6% (3.4; 6.1), 5.3% (4.1; 6.8) and 4.4% (3.5; 5.8), respectively, among men. Among men, the incidence of WPA was 4.6 (3.4; 6.1), 5.3 (4.1; 6.8), and 4.4% (3.5; 5.8), respectively. These incidences were significantly higher among male nurses and aides [11.1 (8.0; 15.4), 12.3 (8.9; 16.6), and 9.3% (6.5; 13.3) during each period] and psychiatric center workers [women: 14.7 (11.2; 19.0), 15.4 (11.8; 19.8), and 12.4% (9.2; 16.6); men: 12.3 (7.2; 20.0), 17.8 (11.6; 26.2), and 14.3% (8.8; 22.4)]. Among women, the risk of WPA was 23% lower in the post-COVID-19 period compared to before the pandemic [aRR = 0.77 (0.64; 0.93)], while the risk during the COVID-19 baseline was not significantly different [aRR = 0.89 (0.74; 1.06)]. Conclusions The COVID-19 pandemic led to an unexpected decrease in first-time WPA against HCWs. However, 5% of HCWs experienced at least one incidence of aggression in the last follow-up year. Healthcare managers should continue to increase the prevention of aggression against HCWs, especially among vulnerable groups with a higher level of incidence.